2009
DOI: 10.1007/s11692-009-9051-1
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Modularity in the Mammalian Skull II: Evolutionary Consequences

Abstract: Changes in patterns and magnitudes of integration may influence the ability of a species to respond to selection. Consequently, modularity has often been linked to the concept of evolvability, but their relationship has rarely been tested empirically. One possible explanation is the lack of analytical tools to compare patterns and magnitudes of integration among diverse groups that explicitly relate these aspects to the quantitative genetics framework. We apply such framework here using the multivariate respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
345
3
57

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(428 citation statements)
references
References 32 publications
19
345
3
57
Order By: Relevance
“…Allometry is known to be a major component of covariation in the mammalian cranium 7 and contributes to its integration and modularity 8 . Indeed, without integration, fundamental functions could be compromised as size changes during ontogeny and in evolution 9,10 .…”
mentioning
confidence: 99%
“…Allometry is known to be a major component of covariation in the mammalian cranium 7 and contributes to its integration and modularity 8 . Indeed, without integration, fundamental functions could be compromised as size changes during ontogeny and in evolution 9,10 .…”
mentioning
confidence: 99%
“…The trend for the face to elongate with allometry has also been noted in mammals (17) and is postulated to be related to heterochrony, an important factor in the evolution of birds from dinosaurs (46) and a demonstrated mode of generating diversity of beak forms in Darwin's finches (6,9). In mammals, it has been shown that integration constrains evolution along paths of least evolutionary resistance, meaning that heterochronic or allometric changes offer a simple mechanism by which evolution can act to produce high disparity (47,48). The fact that two nonsister clades of accipitrid vultures achieve a vulturine morphology solely by increasing skull size provides a new, nonmammalian example of this phenomenon.…”
Section: Discussionmentioning
confidence: 93%
“…A consequence of this mechanism is that skull morphology is highly constrained. Interestingly, animals that demonstrate high levels of integration are less able to respond to shifting selective pressures because they are locked in to a particular dimension of variation (47,49): in this case, size. Consequently, raptors may be particularly vulnerable if changing environmental conditions result in an adaptive peak that they cannot reach by simply sliding along their allometric trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Combining simulations with empirical data has shown that phenotypic integration does influence the direction of interspecific variation (50). For example, simulations using empirically derived covariance matrices from mammal crania have also shown that high integration is associated with lower ability to respond to selection (62), with both the magnitude and direction of response to selection mediated by phenotypic integration ( Fig. 2A) (63).…”
Section: Evolvability and Modularity: The Macroevolutionary Consequenmentioning
confidence: 96%
“…Many studies have tested for correlations between developmental integration, variational integration, and overall variation across taxa to assess the influence of developmental interactions on morphological evolution (18,22,23). Others have simulated the potential effects of trait integration on the ability of populations to respond to selection (50,62). Combining simulations with empirical data has shown that phenotypic integration does influence the direction of interspecific variation (50).…”
Section: Evolvability and Modularity: The Macroevolutionary Consequenmentioning
confidence: 99%